Generation of Neutral Chemically Reactive Species in Low-Pressure Plasma - Primc, Gregor (Frontiers in Physics, 2022)
The surface finish of organic and inorganic materials treated by gaseous plasma usually depends on the fluxes and fluencies of chemically reactive species such as molecular radicals. In low-pressure plasmas, the dissociation of molecules to parent atoms depends on the production rate in the gas phase and on the loss rate on surfaces. The processing will be efficient if the loss rate is minimized. The methods for minimizing the loss rate and thus increasing the processing efficiency are presented and discussed. The dissociation fraction of simple molecules exceeds 10% providing the plasma-facing materials are smooth with a low coefficient for heterogeneous surface recombination. The density of atoms in a plasma reactor increases with increasing pressure reaching a maximum, and decreases with further pressure increase, which is explained by two competing processes. The energy efficiency also exhibits a maximum, which may be as high as 30% if plasma is sustained by electrodeless high-frequency discharges. Optimization of energy efficiency is not only beneficial for the costs of material processing but also for the prevention of excessive heating of treated materials. The latter is particularly important for organic materials because the surface functional groups are not stable but decay with increasing surface temperature.